Tinea corporis by Nannizia gypsea: delayed diagnosis due to unusual presentation, - Juliana de Jesus Soares; Nathalie Andrade Sousa; Luna Azulay-Abulafia; Rosane Orofino Costa (Sociedade Brasileira de Dermatologia, 2021)
Abstract Fungal infections by dermatophytes can present with unusual clinical manifestations, which can cause diagnostic difficulties. The authors present the case of a patient with cutaneous infection by Nanizzia gypsea, initially treated erroneously with topical corticosteroids due to a wrong diagnosis. It was cured after antifungal treatment.